Whole-Genome Sequencing, Phylogenetic and Genomic Analysis of Lactiplantibacillus pentosus L33, a Potential Probiotic Strain Isolated From Fermented Sausages - Stergiou, Odysseas Sotirios; Tegopoulos, Konstantinos; Kiousi, Despoina Eugenia; Tsifintaris, Margaritis; Papageorgiou, Aristotelis C.; Tassou, Chrysoula C.; Chorianopoulos, Nikos; Kolovos, Petros; Galanis, Alex (Frontiers in Microbiology, 2021)
Lactobacillus is a diverse genus that includes species of industrial and biomedical interest. Lactiplantibacillus pentosus, formerly known as Lactobacillus pentosus, is a recently reclassified species, that contains strains isolated from diverse environmental niches, ranging from fermented products to mammalian gut microbiota. Importantly, several L. pentosus strains present health-promoting properties, such as immunomodulatory and antiproliferative activities, and are regarded as potential probiotic strains. In this study, we present the draft genome sequence of the potential probiotic strain L. pentosus L33, originally isolated from fermented sausages. Comprehensive bioinformatic analysis and whole-genome annotation were performed to highlight the genetic loci involved in host-microbe interactions and the probiotic phenotype. Consequently, we found that this strain codes for bile salt hydrolases, adhesins and moonlighting proteins, and for Class IIb bacteriocin peptides lacking the GxxxG and GxxxG-like motifs, crucial for their inhibitory activity. Its adhesion ability was also validated in vitro, on human cancer cells. Furthermore, L. pentosus L33 contains an exopolysaccharide (EPS) biosynthesis cluster, and it does not carry transferable antibiotic resistance genes. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway and CAZymes analyses showed that L. pentosus L33 possesses biosynthetic pathways for seven amino acids, while it can degrade a wide array of carbohydrates. In parallel, Clusters of Orthologous Groups (COGs) and KEGG profiles of L. pentosus L33 are similar to those of 26 L. pentosus strains, as well as of two well documented L. plantarum probiotic strains. Conclusively, L. pentosus L33 exhibits good probiotic potential, although further studies are needed to elucidate the extent of its biological properties.